Wind energy management of a standalone system operating at maximum power point - Hani Albalawi; Sherif A. Zaid; Yonis M. Buswig; Hassan Wedaa El-Rab; Abderrahim Lakhouit; Muhammed Ayas Arshad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In this paper, the management and control of a standalone wind energy system versus variations of wind speed and load are investigated. The system includes a wind turbine coupled to a variable-speed permanent magnet synchronous generator (PMSG), rectifier, boost converter, power inverter, and an energy storage system (ESS). The ESS is a very important part to achieve system stability and support the maximum power point tracking (MPPT) operation. A simple off-line MPPT algorithm is introduced that can be accomplished using the boost converter. The system dynamic model is derived then the control and energy management algorithms are introduced to improve the system performance. The MATLAB platform has been utilized to simulate the proposed system under different disturbances in the load power and wind speed. The results show perfect management of the system energy, good performance of the DC link voltage, stable load voltage, and load frequency.